แนวทางการดำเนินงานในการนำเทคโนโลยีสารสนเทศมาใช้ในโรงเรียนสังกัดเทศบาลนครปฐม - รัชพงษ์ไทย นุชนาฏ; วิเศษศิริ ปองสิน (An Online Journal of Education, 2018)
The objectives of this study were 1) to analyze and 2) to suggest the appropriated guidance for ICT framework under Ministry of Education 2014-2016 for education and implementation in the school under local government. The conceptual framework of the research was based on the indicators of success and failure of the ICT framework implementation model of Woradej Chantasorn including policy factor, human resource factor, administrative factor, environmental factor, planning and control factor, communication factor, resource factor and coordination and cooperation factor. The population of the study were administrators and teachers from 11 schools under local government of Nakhon Pathom. They were asked to respond with questionnaires and interview. The data was analyzed by descriptive statistics. The results from questionnaires revealed that the highest score is engaged in policy factor, the second is engaged in human resource factor, the third is engaged in administrative factor, the forth is engaged in environmental factor, the fifth is engaged in planning and control factor, the sixth is engaged in communication factor, the seventh is engaged in resource factor and the last is engaged in coordination and cooperation factor.